The Mulligan concept of manual therapy 2e : textbook of techniques - Hing, Wayne; Hall, Toby; Mulligan, Brian R (Elsevier, 2020)
A comprehensive and easy-to-follow resource for the manual therapist seeking to improve patients’ movement using pain-free hands-on techniques. The Mulligan Concept is used by health practitioners globally to assist individuals in improving movement restrictions, pain with movement and functional restrictions. The text is divided by body regions, with techniques highlighting key information to assist with clinical reasoning and assessment, patient and practitioner positioning, guidelines for application and further adjustments. Nakladatelská anotace. Kráceno.
Keywords: Musculoskeletal Manipulations; techniky fyzikální terapie; rehabilitační a fyzikální medicína; muskuloskeletální manipulace; manipulace ortopedická; Manipulation, Orthopedic; Physical Therapy Modalities